Laparoscopic management of giant gastrointestinal stromal tumor - Akbulut, S; Ciftci, F; Dirican, A (2018)
Gastrointestinal stromal tumors (GISTs) are the most common non-epithelial (mesenchymal) tumors of the gastrointestinal tract. Although GISTs appear as solid and well-circumscribed lesions in most patients, they may also appear as solid-cystic (mixed) or pure cystic lesions due to reasons like intra-tumor hemorrhage and necrosis in a very small percentage of patients. Hence, cystic GISTs mostly lead to a diagnostic dilemma. In this paper we aimed to report a case of pure cystic giant GIST that was drained percutaneously twice after being misdiagnosed as a mesenteric cyst. An 83-year-old man was operated for a pre-diagnosis of a recurrent mesenteric cyst. The operation was started with the three-trocar laparoscopic technique. Six thousand milliliters of purulent fluid were drained from the cystic lesion. Then, a mini incision was performed above the umbilicus and the cyst and the distal ileal segment where it was originated were removed from the abdominal cavity. After the resection of a 15-cm ileal segment together with the cystic lesion, an intestinal anastomosis was performed. The histopathological and immunohistochemical findings showed that the mass was a GIST (size: 20 cm, mitosis: 3/50 HPF; Ki 67: , CD117: positive, DOG-1: positive). The patient was closely followed without imatinib therapy. C1 [Akbulut, Sami] Inonu Univ, Fac Med, Dept Surg, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey. [Akbulut, Sami] Inonu Univ, Fac Med, Liver Transplant Inst, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey.